Online mindfulness-based interventions to alleviate burnout and related psychological qualities among resident physicians and medical students: A systematic review - Dharmeswari, Made Prabhanika Rahayu; Tondok, Marselius Sampe (Universitas Mercu Buana Yogyakarta, 2024)
This systematic review investigates the effectiveness of online mindfulness-based interventions in addressing burnout and related psychological factors among resident physicians and medical students. The investigation adhered to the guidelines outlined in Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA). A comprehensive literature search was conducted across integrated databases, namely Google Scholar, PubMed, SagePub, and Springer using pertinent keywords. Nine articles met the inclusion and exclusion criteria and were included in the analysis. The results revealed that online mindfulness-based interventions show promising results in alleviating burnout among healthcare professionals and medical students. However, several factors must be considered, and a follow-up measurement is required to maintain its effectiveness. Keyword: Burnout; medical students; mindfulness; online interventions; systematic review.